مظاهر عصرنة القضاء الإداري الفرنسي من خلال تحليل التعديلات الأخيرة للتقنين الفرنسي للعدالة الإدارية - كسير, سليم (University of Eloued جامعة الوادي, 2018)
This study highlighted the recent changes in the French legalization of administrative justice since 2017 in order to identify the modernization of the administrative judiciary in France in response to the requirements of the technology era and to bring the administrative judiciary closer to the citizen as well as finding new mechanisms for solving administrative disputes and rationalizing the use of public funds. In fact, the modernization of the French administrative system is the establishment of the system of remote appeals by eliminating the physical nature of the procedures by relying on modern communication technologies and the establishment of mediation and collective action to reduce the pressure on the administrative judge and the adoption of an internal organization of administrative judicial bodies in order to activate the role of the administrative judiciary.
الملتقى الدولي الثامن: التوجيهات الحديثة للقضاء الإداري ودوره في إرساء دولة القانون 06-07 مارس 2018 جامعة الوادي
Keywords: عصرنة القضاء الإداري الفرنسي، التقنين الفرنسي للعدالة الإدارية